SISTEM PEMBELAJARAN DI SDN CILUBANG DESA BENCOY KECAMATAN CIREUNGHAS SELAMA MASA PANDEMI COVID-19 - Udin Saepudin; rahmat Wisnu perkasa; lastri setiawati; Ghaida Yuthika; Sudin Saepudin; Kurniawan; Anggy Pradifta Junfithrana (Jurnal Abdi Nusa, 2021)
Corona virus is an unexpected outbreak which can be said to be a health crisis, at this time social distancing is very much used to break the chain of transmission of this epidemic so as to do all work and education. Technological developments are very influential in being able to help activities to keep going properly, even if they are done only from home. Everyone is required to be able to use technology which continues to evolve every day. The purpose of this research is to find information about the learning systems and techniques in Cilubang State Schools during the pandemic period and how to respond as education personnel and students to deal with the current pandemic.online